Proximal Nerve Root Involvement in immunoglobulin M Anti–Myelin-Associated Glycoprotein Neuropathy Presenting as Cauda Equina Syndrome. Issue 2 (December 2020) - Fernandes, Marco; Calvão-Pires, Pedro; Caetano, André; Santos, Luís
Abstract : Abstract: Typical distal symptoms in anti–myelin-associated glycoprotein (anti-MAG) neuropathy are believed to be due to the binding of immunoglobulin M to distal nerve terminals. We describe the case of a 56-year-old man diagnosed with immunoglobulin M anti-MAG neuropathy in the setting of Waldenström macroglobulinemia, which developed acute neurological worsening presenting as cauda equina syndrome. Lumbosacral magnetic resonance imaging revealed enlarged nerve roots with diffuse heterogeneous gadolinium enhancement. Treatment with steroids resulted in substantial clinical improvement. Increased recognition of atypical presentations may lead to improved characterization of anti-MAG neuropathy as a more widespread disease.